Social entrepreneurship in rural areas as illustrated by social cooperatives in Poland’s Masovian Voivodeship - Małgorzata Błażejowska (Polityki Europejskie, Finanse i Marketing)
This paper aims to present the social cooperative movement in Poland’s rural areas as illustrated by social cooperatives operating in rural communes of the Masovian Voivodeship. Of the 32 units operating at least since 2014, only 10 have remained on the market. Based on the National Court Register data, the study examined activity profiles, employment levels, activity periods, founding entities and financial situations by using the method of indicators of dynamics and return on sales (ROS). Cooperatives were selected with regard to the legal nature of their founders in order to indicate any differences. The cooperatives established by legal persons had a stable financial situation in the case of 80% of the analysed entities. All of them recorded an increase in revenues in comparison to the year before and 80% of them reported a profit and a positive ROS. 80% of the entities established by natural persons generated a loss from conducted activities and a negative ROS in the last three years of conducted activities. The research results showed that the greatest chances for development were found in cooperatives that were established by legal persons and which rendered services of general interest.